1871 Del. Law 605, § 14 - (:unkn) unknown (General Publisher, 1871)
Placed a duty on commissioners, justices, and constables to suppress, extinguish, and prevent bonfires in the public square of Dover. Also required the suppression and preventing of discharge of guns, pistols, fireworks, or throwing fireballs within the town limits.
--
Keywords: DISCHARGE